Burden of central-line-associated bloodstream infections in 106 Ministry of Health hospitals of Saudi Arabia: a 2-year surveillance study - Alanazi, Khalid H.; Alqahtani, Mohammed; Humayun, Tabish; Alanazi, Adel; Aldecoa, Yvonne S.; Alshanbari, Nasser; El-Saed, Aiman; Bin Saleh, Ghada (International Journal of Infection Control, 2021)
Background: Although the Saudi Ministry of Health (MOH) is managing the majority of inpatient bed capacity in Saudi Arabia, surveillance data for central-line-associated bloodstream infections (CLABSI) have never been reported at a national level. Objectives: To estimate unit-specific CLABSI rates along with central line utilization ratios in MOH hospitals. Additionally, to benchmark such rates and ratios with recognized regional and international benchmarks. Methods: A prospective surveillance study was conducted in 106 MOH hospitals between January 2018 and December 2019. The data from 14 different types of intensive care units (ICUs) were entered into the Health Electronic Surveillance Network (HESN) program. The surveillance methodology was similar to the methods of the US National Healthcare Safety Network (NHSN) and the Gulf Cooperation Council (GCC) Center for Infection Control. Results: During the 2 years of surveillance in ICU setting covering 1,475,177 patient-days and 475,913 central line-days, a total of 1,542 CLABSI events were identified. The overall CLABSI rate was 3.24 (95% confidence interval [CI], 3.08–3.40) per 1,000 central line-days, and the overall central line utilization ratio was 0.32 (95% CI, 0.322–0.323). CLABSI-standardized infection ratios in HESN hospitals were very similar (1.01) to GCC hospitals, but 3.2 times higher than NHSN hospitals and 36% lower than International Nosocomial Infection Control Consortium (INICC) hospitals. Central-line-standardized utilization ratio in MOH hospitals was 15–30% lower than the three benchmarks. Conclusions: The overall CLABSI rate was 3.24 per 1,000 central line-days, and the overall central line utilization ratio was 0.32. MOH CLABSI rates were very similar to GCC hospitals, but higher than NHSN hospitals and lower than INICC hospitals. MOH central line utilization is slightly lower than the three benchmarks.